O uso de tecnologias móveis no ensino de frações para alunos do ensino fundamental nos anos finais. - Nascimento, Edvaldo Lopes do (2019)
With the development of research in mathematics education, the need for new teaching strategies that lead the student to participate in the whole process, in a more active and constructive way, requires a teacher role with pedagogical interventions that favor reflexive and coherent practices with the protagonism of the student (Costa and Vieira, 2006). Technology should help teachers in the most sensitive aspects of teaching these numbers, in motivating and constructing terms and definitions, if we analyze the private schools of the more developed regions, investment in technology is an increasingly present reality, which have become variables contribute to the students' learning process. In this study proposal the research was carried out with 6th grade students from a private school located in the western zone of São Paulo, to which we find a very different reality from most of the schools whose technological structure is available in the classroom for teachers and students. In a practical way, the research took place in 7 meetings with an average of 20 students aged between 10 and 11 years. The objective of this work is to search through the use of an educational application, called "One Room", which has as a characteristic to treat fractional numbers to mediate activities so that there is an advance in the construction of concepts of fractional numbers. From the results that relate the Theories of Didactic Situations, the results point to real indications of the influence of the activities in the improvement of students' perception in the concepts of fraction and its operations.